2011
DOI: 10.1002/jmri.22570
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of aortic arch pulse wave velocity in cardiovascular MR: Comparison of transit time estimators and description of a new approach

Abstract: Purpose: To investigate the efficiency of a new method (TT-Upslope) for transit time (Dt) estimation from cardiovascular MR (CMR) velocity curves. Materials and Methods:Fifty healthy volunteers (40 6 15 years) underwent applanation tonometry to estimate carotid-femoral pulse wave velocity (cf-PWV) and carotid pressure measurements, and CMR to estimate aortic arch-PWV and ascending aorta distensibility (AAD). The Dt was calculated with TT-Upslope by minimizing the area delimited by two sigmoid curves fitted to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
85
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(94 citation statements)
references
References 34 publications
6
85
1
Order By: Relevance
“…With our curve-fitting technique we found that half maximum velocity was more accurate than the foot of the slope owing to errors in extrapolating the intersection of baseline and upstroke velocities. There is precedent for using the point of half maximum to estimate arrival time at MR imaging (23,24), and this methodology has been shown in a recent study to have higher correlation with age and carotid femoral PWV (25). Further studies are needed to affirm prognostic and therapeutic implications of our findings.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…With our curve-fitting technique we found that half maximum velocity was more accurate than the foot of the slope owing to errors in extrapolating the intersection of baseline and upstroke velocities. There is precedent for using the point of half maximum to estimate arrival time at MR imaging (23,24), and this methodology has been shown in a recent study to have higher correlation with age and carotid femoral PWV (25). Further studies are needed to affirm prognostic and therapeutic implications of our findings.…”
Section: Discussionmentioning
confidence: 83%
“…This distance was termed the aortic arch distance. PWV was calculated by dividing the aortic arch distance by the transit time, which was calculated as the time between the ascending and descending upstroke velocities at half maximum (23)(24)(25). Further details regarding aortic arch PWV measurement are shown in the Figure. Cardiovascular risk factors.-Variables were assessed at entry into DHS-1.…”
Section: Predictor Variablesmentioning
confidence: 99%
“…All analyses were performed using validated software (ART-FUN, Inserm, Paris). 26,27 The path length was defined on the anatomic images to create a 3D Bezier curve through the centerline of the aorta intersecting the plane at which flow measurements had been obtained.…”
Section: Image Analysismentioning
confidence: 99%
“…27 Volumetric analysis of the LV cine images was performed with CMRtools (Cardiovascular Imaging Solutions, London, United Kingdom) using semiautomated segmentation of the left ventricle with tracking of the mitral and aortic valves. LV mass and cardiac output were derived from these data.…”
Section: Image Analysismentioning
confidence: 99%
“…However, the optimal method for estimation of transit time from the resultant velocity curves remains under review [114]. Research is currently focused on a revision of the traditional 2-slice method to a two-directional in-plane velocity-encoded CMR covering the entire aorta in 3 parallel oblique-sagittal slices and, more recently, to a 4-slice breath-hold throughplane velocity-encoded CMR [115,116].…”
Section: Post Surgical Assessmentmentioning
confidence: 99%